Let P ( x ) be a polynomial of the form P ( x ) = x n + x n − 1 + 1 , where n is the smallest possible integer number ≥ 2 0 2 0 such that P ( x ) = ( x 2 + x + 1 ) Q ( x ) , where Q ( x ) is a polynomial. Find the number
2 ℜ ( Q ( − 2 1 + i 2 3 ) ) − 2 .
Notation: ℜ ( ⋅ ) denotes the real part function .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution!
Let us define the sequence of polynomials
P
n
(
x
)
=
x
n
+
x
n
−
1
+
1
. It is easy to see that
P
n
(
x
)
=
(
x
2
+
x
+
1
)
(
x
n
−
2
−
x
n
−
4
)
+
P
n
−
3
(
x
)
,
n
≥
5
.
(
∗
)
From the previous recurrence relation, we have that
(
x
2
+
x
+
1
)
∣
P
n
(
x
)
if and only if
(
x
2
+
x
+
1
)
∣
P
n
−
3
(
x
)
for any integer
n
≥
5
.
Notice that
P
2
(
x
)
=
x
2
+
x
+
1
,
and then it is divisible by
(
x
2
+
x
+
1
)
,
but
P
3
(
x
)
and
P
4
(
x
)
are not divisible by
(
x
2
+
x
+
1
)
.
Therefore,
(
x
2
+
x
+
1
)
is a factor of
P
n
(
x
)
if and only if
n
=
3
k
+
2
,
where
k
is any non-negative integer. Then
P
(
x
)
=
P
2
0
2
1
(
x
)
.
Now for any
n
integer greater than or equal to 2 we define
Q
n
(
x
)
=
x
2
+
x
+
1
P
n
(
x
)
.
Obviously,
Q
(
x
)
=
Q
2
0
2
1
(
x
)
and from the recurrence relation (*), we get that
Q
n
(
x
)
=
x
n
−
2
−
x
n
−
4
+
Q
n
−
3
(
x
)
,
where
n
is any integer number that is greater than or equal to 5.
Then we have the following
Q 5 ( x ) = x 3 − x + Q 2 ( x ) Q 8 ( x ) = x 6 − x 4 + Q 5 ( x ) Q 1 1 ( x ) = x 9 − x 7 + Q 8 ( x ) . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . Q 2 0 2 1 ( x ) = x 2 0 1 9 − x 2 0 1 7 + Q 2 0 1 8 ( x ) Adding all these equalities and cancelling repeated terms, we get that Q 2 0 2 1 ( x ) = ( x 3 + x 6 + . . . + x 2 0 1 9 ) − x ( 1 + x 3 + . . . + x 2 0 1 6 ) + Q 2 ( x ) . Evaluating the last formula at − 2 1 + i 2 3 = e 3 2 π i , using that ( e 3 2 π i ) 3 k = 1 , and that Q 2 ( e 3 2 π i ) = 1 , we can conclude that Q 2 0 2 1 ( − 2 1 + i 2 3 ) = 6 7 4 − 6 7 3 ( − 2 1 + i 2 3 ) = 1 0 1 0 . 5 − 6 7 3 i 2 3 . Then the answer for this question is 2 0 1 9 .
Once you know that P ( x ) = x 2 0 2 1 + x 2 0 2 0 + 1 and realize that plugging in ω to the factorization gives 0 = 0 , it is also possible to tease out Q ( ω ) using an algebraic derivative (which follows all the same power rules from calculus and are valid via complex analysis; FToA gets its proof there anyway) on the polynomial P : 2 0 2 1 ω 2 0 2 0 + 2 0 2 0 ω 2 0 1 9 = ( 2 ω + 1 ) Q ( ω ) + 0 ( ω 2 + ω + 1 ) Q ′ ( ω ) . From here it follows that Q ( ω ) = 2 ω + 1 2 0 2 1 ω + 2 0 2 0 , rationalize, take the real part to get the answer to the question which is 2 0 1 9 .
Problem Loading...
Note Loading...
Set Loading...
Since we want P ( ω ) = 0 we must have n ≡ 2 ( m o d 3 ) , and so n = 2 0 2 1 and then ( x 3 − 1 ) Q ( x ) = ( x − 1 ) P ( x ) = ( x − 1 ) ( x 2 0 2 1 + x 2 0 2 0 + 1 ) = x 2 0 2 2 − x 2 0 2 0 + x − 1 = ( x 3 − 1 ) ( n = 0 ∑ 6 7 3 x 3 n − x n = 0 ∑ 6 7 2 x 3 n ) so that Q ( x ) = n = 0 ∑ 6 7 3 x 3 n − x n = 0 ∑ 6 7 2 x 3 n and hence Q ( ω ) = 6 7 4 − 6 7 3 ω so that R e [ Q ( ω ) ] = 6 7 4 + 2 6 7 3 making the answer 2 × 6 7 4 + 6 7 3 − 2 = 2 0 1 9 .